Shock and economic growth in Malaysia - Dahalan, Jauhari; Mohd Mustafa, Muszafarshah (Universiti Utara Malaysia, 2010)
The objective of the study is to examine shocks and economic growth using an a-theoretical approach. An a-theoretical framework for studying shocks and economic growth was possible through the use of VAR method.We performed stationarity, causality and cointegration tests in order to achieve an appropriate model specification in estimating real relationships among the selected variables. The unitroot tests found that all except one of the variables were nonstationary and were integrated of order one, I(1).The Granger causality tests found broad money supply, real exchange rate and inflation were Granger caused by variables neither jointly nor individually.We implemented the Johansen cointegration procedure to test for cointegration.The test found one cointegrating relationships among the variables, which implied that the system was stable in one way.Based on the test results, a cointegrated VAR approach was used to analyse relationships among variables using the system’s responses to random shocks.This analysis formed the basis of discussion of the economic implications.This study found that fiscal policy did provide the necessary impetus to improve growth over the long term, but monetary policy did not result in the expected direction of effect.It was found that investment expenditure by government was sufficient to cause a significant long term economic growth. There was a lack of clarity on the effects of monetary policy changes as a result of dual objectives of the policy, price control and maintenance of the exchange rate.Given the lack of clarity, over emphasis on inflation control may not be desirable as a result of the constraint placed on economic growth. Additional insights on the effects of monetary policy are necessary through a detailed study using a similar empirical method.In addition, trade was found to be a significant source of economic growth.A focus of policy on trade development can be expected to contribute to economic development in the long term.